The development of prosodic focus marking in French - Destruel, Emilie; Lalande, Louise; Chen, Aoju (Frontiers in Psychology, 2024)
Introduction French is traditionally described as a language favoring syntactic means to mark focus, yet recent research shows that prosody is also used. We examine how French-speaking children use prosody to realize narrow focus and contrastive focus in the absence of syntactic means, compared to adults. Method We elicited SVO sentences using a virtual robot-mediated picture-matching task from monolingual French-speaking adults (N = 11), 4- to 5-year-olds (N = 12), and 7- to 8-year-olds (N = 15). These sentences were produced with narrow focus on either the subject or the object and contrastive focus on the object. Results Linear mixed-effects logistic regression modeling on duration, mean intensity, mean pitch, and pitch range of the subject and object nouns showed that the 4- to 5-year-olds did not use any of these prosodic cues for focus marking but the 7- to 8-year-olds distinguished narrow focus from non-focus through an increase in duration, mean intensity and to a lesser degree, mean pitch in the object nouns, largely similar to the adults, and tended to use mean pitch for this purpose in the subject nouns, different from the adults, who used duration. Discussion Our study corroborates previous findings that French-speaking 4- to 5-year-olds do not use prosody for focus. Further, it provides new evidence that 7- to 8-year-olds use prosody to mark narrow focus on the object in a more adult-like manner than narrow focus on the subject, arguably caused by a more dominant role of syntactic means in the subject position in French. Together, these findings show that syntax-dominance can influence both the route and the rate of acquisition of prosodic focus marking.